2016
DOI: 10.4314/tjpr.v15i11.21
|View full text |Cite
|
Sign up to set email alerts
|

Pinoresinol diglucoside exhibits protective effect on dexamethasone-induced osteoporosis in rats

Abstract: , ,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…These three diglucosides were present in sesame seeds in comparable concentrations. However, only the latter compound, with glucose molecules attached to different methoxyphenol moieties of pinoresinol, was used in all biomedical studies on pinoresinol diglucoside that we are aware of (e.g., [ 107 , 108 , 109 ]).…”
Section: Chemistry Of Sesame Lignansmentioning
confidence: 99%
See 1 more Smart Citation
“…These three diglucosides were present in sesame seeds in comparable concentrations. However, only the latter compound, with glucose molecules attached to different methoxyphenol moieties of pinoresinol, was used in all biomedical studies on pinoresinol diglucoside that we are aware of (e.g., [ 107 , 108 , 109 ]).…”
Section: Chemistry Of Sesame Lignansmentioning
confidence: 99%
“…Pinoresinol diglucoside alleviated osteoporosis in rats [ 107 ]; unfortunately, only one of the three isomers was tested (see Section 2.1.4 ). Sesamol can protect cartilage against degradation (chondroprotective effect) [ 359 ].…”
Section: Biological Activities Of Lignansmentioning
confidence: 99%
“…Osteoporosis is a chronic bone disease characterized by decreased bone mass or bone mineral density (BMD), deterioration of bone architecture, and enhanced susceptibility to fracture. Osteoporosis disease is the most critical health issue after cardiovascular disease (1)(2)(3). The frequency of osteoporosis has increased worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Phenylethanoid glucosides were more abundant than the other phytochemical groups. Chlorogenic acid, forsythoside A, pinoresinol diglucoside, quercetin, rutin, and salidroside have been shown to exert anti-osteoporotic and anti-osteolytic effects in animal models [28,29,30,31,32,33], and other studies have reported the inhibitory effects of chlorogenic acid, forsythoside A, matairesinol, quercetin, and rutin on osteoclast differentiation [28,30,34,35]. However, forsythoside B, forsythoside E, forsythin, phillygenin, and pinoresinol glucoside have not been reported in bone metabolism.…”
Section: Resultsmentioning
confidence: 99%